Challenges and opportunities of edible vegetable oil market in China - HE Dong-ping; LUO Zhi; GAO Pan (Liang you shipin ke-ji, 2020)
The edible vegetable oil industry of China is developing rapidly and still faced with serious challenges.Based on the analysis of current situation of edible oil market development in China, insufficient of hazardous substances detection in the process of processing, lacking of systematic investigation about small varieties oils marketization, insufficient of nutritional evaluation of vegetable oil and deficient of special edible blending oil research for special population, in this paper, we proposed the opportunities and prospects in Chinese market of edible vegetable oil, the accurate and appropriate processing mode of fats and oils, systematically development of small varieties oils, research of the nutritive value of edible oils, and development of special edible blend oils for special populations.We hope this review would provide useful references and suggestions for promoting the high quality development of oil processing industry in China.